If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 14 = 46 Reorder the terms: 14 + 2x = 46 Solving 14 + 2x = 46 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 2x = 46 + -14 Combine like terms: 14 + -14 = 0 0 + 2x = 46 + -14 2x = 46 + -14 Combine like terms: 46 + -14 = 32 2x = 32 Divide each side by '2'. x = 16 Simplifying x = 16
| 1.8n=2.7 | | 48=3x+6 | | 41=5x+11 | | Log[4](2x)+log[4](x+7)=2 | | 3g(3x-y)-(3x-y)= | | 3.4=0.2z | | 10x+7=5x+10 | | 28=4p | | 2/5x-5=b-3/5 | | 9=2c | | 1.2z=9.6 | | 2/x/5=0 | | 2-i/2+5i | | 3/8c=24 | | 5a+-14=p+13 | | 5.4=2.7d | | 0.63*0.05= | | x(x-3)=x-3 | | 4t^2-5t-50=0 | | 6+(-2)-76=-142 | | -(-8m+4)=-12(m+2) | | 5.4=2.7 | | (x+9)*(x+9)=0 | | 0.9p^2-8p+3.3-2=0 | | 0.630.05= | | B/7=14 | | 9c^2-42c+49=0 | | -2(17x-4)+7(5x-4)-4=3-4 | | -(r+4)+9r=-1+8r | | 2/3(x-6)=4/5x-1 | | 9c-42+49=0 | | 5x+2x-27=x+100 |